New product development in globalization era - Balakrishnan, Bavaani (2018)
Currently, new product development is important in order for firms to grow and successful.Successful new product development is essential for any business if it hopes to exist continuously. Globalization effect which increases competition, cost cutting and time reduction has been pressing industrial players to undertake a structured way to improve the process effectively.Therefore, many companies invested a huge of capital in defining a product line demand that can be translated into the market demand and needs. However, many new product development projects failed where many new products which were introduced into the market does not run successfully as planned.The reason is it does not meet customers‟ expectation despite all the effort. Hence, this conceptual paper is about the discussion of the new product development in globalization era.It will affect the influence of technology and innovation in new product development.A review of the literature on product lifecycle, new product development, technology and innovation along with new product development theories discussed in this paper.This paper expected to gives significant contribution in understanding customers‟ needs and wants so that industry practices to focus resources in promote technology and innovation in new product development which more likely to be accepted by customers.